Fashion TV and the Motivation of His Audience - Pavlushina, Margarita I.; Dautova, Rezida V. (Journal of History Culture and Art Research, 2017)
The beginning of the 21st century is characterized not only by important historical events in the world, but also by the changes in value norms and priorities. Television, being the most mass and accessible means of information, reflects these changes directly or indirectly. One of the significant trends of modern media is the development of an entertainment segment, which is present on television in the form of special formats and a specialized content. It is necessary to create special conditions for the permanent demonstration of their events, symbols and samples for the development of fashion, as the reflection of public and cultural content and as the means of search for a person's identity. Television has such natural features that provide fashion industry a unique platform for the development of a global fashionable space and intercivilizational communication. Fashion-TV complements the television picture of the world, influencing the spread of fashion trends and the development of a certain culture of behavior and lifestyle among TV viewers. Fashion-TV, as the combination of specialized Fashion channels and TV projects dedicated to fashion and human beauty on Russian social, political and entertainment channels, is primarily the carrier of information about modern fashion trends in clothing that influences the change of a person social-cultural image. This article the hypothesis of modern fashion TV has a blurred target audience with pronounced gender characteristics and a developed motivation. The article presents the results of the study conducted on the basis of the Kazan Federal University for two years.